Diversity Management: Critical Pedagogy in Nepalese Education - Pant, Khagendra Raj (KMC Journal, 2024)
This article delves into the realm of critical pedagogy, a dynamic educational approach designed to cultivate critical thinking skills among students. It explores the relevance of critical pedagogy emphasizing critical thinking and social justice, aligns seamlessly with managing diversity in classrooms, fostering inclusive environments and empowering students to engage with diverse perspectives. It critically underscores the vital role played by critical pedagogy in effectively managing diversity within educational settings. Drawing from extensive literature and the author's insights, it offers a valuable tool to address the complexities of contemporary classrooms. The article significantly contributes to the ongoing discourse on educational approaches by highlighting the transformative impact of critical pedagogy, advocating for its integration into school curricula, and emphasizing the collaborative roles of both teachers and students. Through this comprehensive exploration, the article positions critical pedagogy as an indispensable framework for fostering inclusive and equitable educational environments in the face of diverse challenges.